2020
DOI: 10.1186/s13020-020-00407-w
|View full text |Cite
|
Sign up to set email alerts
|

The drug likeness analysis of anti-inflammatory clerodane diterpenoids

Abstract: Inflammation is an active defense response of the body against external stimuli. Long term low-grade inflammation has been considered as a deteriorated factor for aging, cancer, neurodegeneration and metabolic disorders. The clinically used glucocorticoids and non-steroidal anti-inflammatory drugs are not suitable for chronic inflammation. Therefore, it’s urgent to discover and develop new effective and safe drugs to attenuate inflammation. Clerodane diterpenoids, a class of bicyclic diterpenoids, are widely d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 119 publications
0
14
0
Order By: Relevance
“…Hautriwaic acid, isolated from Mexican medical plant, Dodonaea viscosa, also reduced TPA-induced ear oedema in mice by 60.2%, 70.2%, and 87.1% at 0.25, 0.5, and 1.0 mg/ear concentrations [138]. When Feng et al (2020) evaluated the 'drug-likeliness' of 65 anti-inflammatory clerodane diterpenoids (compared with marketed drugs) using SwissADME, a web-based tool by the Swiss Institute of Bioinformatics [267], many of them fulfill parameters within SwissADME [268]. They found that a lactone ring between C-18 and C-19 is mainly responsible for anti-inflammatory activity.…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%
“…Hautriwaic acid, isolated from Mexican medical plant, Dodonaea viscosa, also reduced TPA-induced ear oedema in mice by 60.2%, 70.2%, and 87.1% at 0.25, 0.5, and 1.0 mg/ear concentrations [138]. When Feng et al (2020) evaluated the 'drug-likeliness' of 65 anti-inflammatory clerodane diterpenoids (compared with marketed drugs) using SwissADME, a web-based tool by the Swiss Institute of Bioinformatics [267], many of them fulfill parameters within SwissADME [268]. They found that a lactone ring between C-18 and C-19 is mainly responsible for anti-inflammatory activity.…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%
“…urticaria, pruritus, angioedema, gastrointestinal symptoms or bronchospasm. PARs usually occur upon the application of drugs, functional foods or food additives, which has been a serious public health concern [1,2]. MAS-related G protein-coupled receptor-X2 (MRGPRX2) has been found to mediate PARs [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…2 Clerodane diterpenoids are isolated from a wide range of plants with anti-inflammatory, antibacterial, cardioprotective, immunomodulatory, antiviral and other biological activities. [3][4][5][6][7][8] Approximately 25% of clerodanes have an H-10/H 3 -19 cis ring fusion and are typically produced from the Menispermaceae family; 9 for example, tinosinenoside A and B, tinospinoside D and E and cordifolide A-C were obtained from the genus Tinospora of the Menispermaceae family. [10][11][12] Tinospora crispa, belonging to the genus Tinospora of the Menispermaceae family, is rich in clerodane diterpenoids and has attracted considerable attention.…”
Section: Introductionmentioning
confidence: 99%